Penerapan Strategi Brand Equity Sebagai Identitas Produk Keripik - Hendra Halim Saputra; Uus MD Fadli; Laras Ratu Khalida (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
Brand equity strategy is a strategy in developing appropriate, attractive and effective brand products. The purpose of this study is to explain the five strategic components of brand equity, namely the application of perceived quality strategy, brand awareness strategy, brand association strategy, brand loyalty strategy, and other proprietary strategies on Soulmate Banana chips which act as product identity and to differentiate them from chips. similar. The study was conducted using a qualitative approach and the data were analyzed using content analysis. Primary data obtained through interviews, observation and documentation. Interviews were conducted with the CEO of UMKM Sarana Snack (P) and 2 consumers (W1 and W2). Secondary data obtained through library research. The research was conducted on Soulmate Banana chips products located in Klari - Karawang. The results show that the brand equity strategy that has been applied to the Soulmate Banana chip product has been successful because the product offered is considered superior to product quality so that it gets a good response by the market as evidence of increasing its brand equity.